The Impact of Public Investment on Economic Growth in Pakistan (The Pakistan Development Review, 2006)
This paper explores the role of public investment in the process of economic growth, in the context of Pakistan’s economy, using the vector autoregressive approach (VAR). Based on theoretical considerations, the model also includes private investment and public consumption besides public investment. The results show that growth is largely driven by private investment and that no strong inference can be drawn from the effects of public investment and public consumption on economic growth. JEL Classification: E2, 04. Keywords: Public Investment, Economic Growth.